MSMEs DIGITAL MARKETING AND ENTREPRENEURSHIP'S FACTOR OF PERFORMANCE: JAMBI (INDONESIA) PERSPECTIVE - Usmayanti, Vivi; Pangestu, Mira Gustiana (UNIVERSITAS NEGERI SURABAYA, 2022)
This research investigates the entrepreneurial dimension, innovation, and digital marketing on market and finance performance. These research samples consist of 260 MSME actors in the city of Jambi. This study employs the Likert scale to measure construct variables in order to test their validity and reliability. The data and hypothesis of this research were examined using partial least square (PLS). The findings of this study indicate that entrepreneurial factor influences innovation and digital marketing positively. Innovation and digital marketing positively impact the performance of MSMEs. However, innovation and digital marketing have no relationship.